2007
DOI: 10.1002/art.22843
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in serum type ii collagen biomarkers predict radiographic progression at one year in inflammatory arthritis patients after biologic therapy

Abstract: Objective. To investigate whether short-term changes in serum biomarkers of type II collagen degradation (C2C) and types I and II collagen degradation (C1,2C), as well as the biomarker for the synthesis of type II procollagen (CPII) can predict radiographic progression at 1 year following initiation of biologic therapy in patients with inflammatory arthritis.Methods. Serum levels of biomarkers were measured at baseline and at 1, 3, 6, 9, and 12 months after initiation of biologic therapy. A composite score ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 38 publications
2
44
1
1
Order By: Relevance
“…Further, we showed that a direct longitudinal relationship exists between clinically perceptible signs of arthritis and degradation of CTX-I and especially CTX-II 14. These and other studies1517 suggest that in RA urinary excretion of CTX-II and other cartilage degradation markers most likely represents joint cartilage, whereas excretion of CTX-I, less prominently associated with clinical signs of arthritis, most likely represents both generalised and localised bone loss 18 19…”
Section: Introductionsupporting
confidence: 72%
“…Further, we showed that a direct longitudinal relationship exists between clinically perceptible signs of arthritis and degradation of CTX-I and especially CTX-II 14. These and other studies1517 suggest that in RA urinary excretion of CTX-II and other cartilage degradation markers most likely represents joint cartilage, whereas excretion of CTX-I, less prominently associated with clinical signs of arthritis, most likely represents both generalised and localised bone loss 18 19…”
Section: Introductionsupporting
confidence: 72%
“…It is known that collagen biomarker and MMP levels predict radiographic progression of RA, and therefore may act as a prognostic biomarker. 135,136 A study with the primary objective of attempting to understand more about the mechanism of action of methotrexate (19 subjects) and leflunomide (16 subjects) demonstrated that MMP-1 was significantly reduced by both. The level of TIMP-1 was significantly reduced in the leflunomide-treated patients, but not the methotrexate-treated patients.…”
Section: Mediators and Products Of Bone Cartilage And Tissue Degradamentioning
confidence: 99%
“…Mullan et al [43] showed that short-term change in serum biomarkers of type 2 collagen degradation (C2C), types 1 and 2 collagen degradation (C1,2C), and the biomarker for type 2 procollagen synthesis (CPII) correlated with radiographic progression following initiation of biologic therapy in patients with RA and psoriatic arthritis. Oneyear radiographic progression was predicted by increases in serum C2C at 1 month (P = 0.031) and clinical remission by reduction in serum levels of C2C (P = 0.008) and C1,2C (P = 0.036) at 1 month.…”
Section: Cartilagementioning
confidence: 99%